PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER JUJUR PADA PESERTA DIDIK - Jihad, Lalu Muhammad Samsul; Iwan Hermawan; M. Makbul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character. One character trait that must be instilled from an early age is honesty. In today's digital age, students face various challenges, such as easy access to information, the widespread spread of fake news, and the practice of cheating online. Therefore, Islamic Religious Education (PAI) needs to be a means of instilling the values ​​of honesty through instruction, teacher role models, and daily habits. This study used a library research method, reviewing various literature related to character education in Islam. The results of the study indicate that the success of developing an honest character is influenced by collaboration between teachers, families, schools, and the community. Islamic Religious Education not only teaches religious knowledge but also guides students to practice Islamic values ​​in their daily lives.